WORK POSTURE RELATIONS WITH MUSCULOSKELETAL DISORDERS IN DUMP TRUCK OPERATOR AT PT HARMONI PANCA MAIN - Tutug Bolet Atmojo; Seviana Rinawati (Journal of Industrial Hygiene and Occupational Health, 2017)
Improper work posture may affect waist and back pain as well as disruption of the muscularkeletal system. The results of estimates published by NIOSH show that the cost of compensation for musculoskeletal complaints has reached 13 billion dollars annually. This study aims to determine the relationship of work posture with lumbar pain and severity of Muskuloskeletal Disorder at Dump Truck Operators Production Part at PT Harmoni Panca Utama Site East Kalimatan. This research is an analytic survey research with cross sectional design. The population of this research is the dump truck operator in the production section of PT Harmoni Panca Utama Site East Kalimantan totaling 150 people. The number of samples is determined by Purposive Sampling Technique. The instruments used in this study were questionnaires, Nordic Body Map Questioner questionnaires, Video Record and Work Posture Images, a low back pain complaint questionnaire. The data analysis technique used is Spearman rank associative test. Characteristics of respondents in the form: age, employment and BMI have no relationship with the severity of musculoskeletal disorders. The result of spearman rank test analysis between work posture and severity of musculoskeletal disturbance was obtained on peaceful site (p = 0.47) and site singlurus (p = 0.43). Keywords: Work posture, Low back pain, Musculoskeletal